Tourism and problems that come with it - Korneychuk, Alexander (My University, 2014)
Tourism can create great pressure on local resources such as energy, food, land and water that may already be in short supply.
Keywords: туризм; проблеми; природне середовище; ресурси; окружающая среда; проблемы; ресурсы; tourism industry; problems; natural environment; resources; кафедра іноземних мов професійного спрямування